2020
DOI: 10.14738/assrj.75.8163
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Science Learning Model for Higher Education of Bachelor Elementary School Teacher Education Program in Distance Learning

Abstract: This research is the second year of a three-year research plan and the development of a new generation of Universitas Terbuka (UT) learning material models for natural science learning courses in elementary schools for higher education of bachelor elementary school teacher education program at the Faculty of Teacher Training and Education. The research design in this research is a combination of the major steps in the R&D cycle with the steps of the system approach to the model of educational R&D. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…This resulted in the company being unable to pay off debt and interest. This accords with research by Laksmi and Budiartha (2020), Setiawan (2009), Sari et al (2012) and Budiastra et al (2020), which found that debt policy has a positive and significant effect on firm value.…”
Section: 1supporting
confidence: 89%
“…This resulted in the company being unable to pay off debt and interest. This accords with research by Laksmi and Budiartha (2020), Setiawan (2009), Sari et al (2012) and Budiastra et al (2020), which found that debt policy has a positive and significant effect on firm value.…”
Section: 1supporting
confidence: 89%
“…The existence of distance learning has become the right choice, especially if the individuals and organizations that will organize the learning have limited time and certain distance (Mishra et al, 2020). As done by many schools, universities and institutions in today's era, distance learning can become the best choice to access the education quickly and easily (Budiastra et al, 2020;Churiyah et al, 2020;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%